Using Word Recognition Instruction and Visual Aids to Enhance Malaysian Primary ESL Learners’ Vocabulary Achievement - Zachary Farouk Chai; Norhidayu Binti Rosman; Mohd Fazri Bin Basri (Journal of English Language Teaching and Learning (JETLE), 2021)
Vocabulary is considered as an essential component of language teaching and learning, and its mastery is significant for all language learners. The process of learning vocabulary is sometimes referred to as vocabulary acquisition. In light of this, teachers need to conduct appropriate and enjoyable activities when teaching vocabulary. Effective techniques and interesting vocabulary materials are imperative especially for primary school ESL learners. This study aimed to determine the efficacy of employing word recognition instruction and visual aids in teaching action verbs to primary school learners in one of the primary schools in Semporna, Sabah, Malaysia. The overall number of participants in the research was 50, and they represented a mixed abilities group of learners. They were randomly assigned into experimental and control groups of 25. The experimental group used word recognition instruction and visual aids to learn new vocabulary (action verbs), while the control group used traditional memorisation instruction to learn the same vocabulary. Following these instructions, the two groups were evaluated (Post-test). The study's findings indicated that the experimental group outperformed the control group. Additionally, it recommends that English language teachers consider word recognition instruction and visual aids as successful vocabulary teaching strategies.